Role of the carbonyl group of the (6–4) photoproduct in the (6–4) photolyase reaction - Yamamoto, Junpei (2009)
The (6–4) photoproduct, which is one of the major UV-induced DNA lesions, causes carcinogenesis with high frequency. The (6–4) photolyase is a flavoprotein that can restore this lesion to the original bases, but its repair mechanism has not been elucidated. In this study, we focused on the interaction between the enzyme and the 3’ pyrimidone component of the (6–4) photoproduct, and prepared a substrate analog in which the carbonyl group, a hydrogen-bond acceptor, was replaced with an imine, a hydrogen-bond donor, to investigate the involvement of this carbonyl group in the (6–4) photolyase reaction. UV irradiation of oligodeoxyribonucleotides containing a single thymine–5-methylisocytosine site yielded products with absorption bands at wavelengths longer than 300 nm, similar to those obtained from the conversion of the TT site to the (6–4) photoproduct. The nuclease digestion, MALDI-TOF mass spectrometry, and the instability of the products indicated the formation of the 2-iminopyrimidine-type photoproduct. Analyses of the reaction and the binding of the (6–4) photolyase using these oligonucleotides revealed that this imine analog of the (6–4) photoproduct was not repaired by the (6–4) photolyase, although the enzyme bound to the oligonucleotide with considerable affinity. These results indicate that the carbonyl group of the 3’ pyrimidone ring plays an important role in the (6–4) photolyase reaction. Based on these results, we discuss the repair mechanism.